2014
DOI: 10.5455/2320-6012.ijrms20140506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum levels of calcium and magnesium among preeclamptic and normotensive pregnant women at Nnamdi Azikiwe University Teaching Hospital, Nnewi, Nigeria

Abstract: Pre-eclampsia refers to a syndrome of new onset of hypertension and proteinuria after 20 weeks of gestation in a previously normotensive woman. 1 Hypertension associated with pregnancy is the most common medical risk for maternal morbidity and mortality. 2 Pre-eclampsia has been dubbed the "disease of theories" because of the multiple hypothesis have been proposed to explain its occurrence. 3 Despite its prevalence and severity, the pathophysiology of this multisystemic disorder is still poorly understood. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 15 publications
9
22
1
Order By: Relevance
“…This suggests a strong association between deficiency of this mineral and outset and progression of preeclampsia. 13 Our findings are similar to many former studies by Onyegbule et al, 5 Sultana et al, 9 Sirajwala et al, 11 Akhtar et al, 13 and Moholkar et al 15 In contrast, some researchers did not demonstrate significant difference between the two groups. 16,17 These contrasting findings may be due to differences in genetic pool of population, method of sample collection, storage and processing of sample, and method of analysis.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This suggests a strong association between deficiency of this mineral and outset and progression of preeclampsia. 13 Our findings are similar to many former studies by Onyegbule et al, 5 Sultana et al, 9 Sirajwala et al, 11 Akhtar et al, 13 and Moholkar et al 15 In contrast, some researchers did not demonstrate significant difference between the two groups. 16,17 These contrasting findings may be due to differences in genetic pool of population, method of sample collection, storage and processing of sample, and method of analysis.…”
Section: Discussionsupporting
confidence: 72%
“…1 Evidences have shown that alterations in the maternal serum levels of some minerals may be implicated in the pathogenesis of preeclampsia. 5 Alterations in calcium homeostasis during pregnancy is more significant in this regard.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between preeclampsia and nutritional deficiencies has been well established; studies have persistently and consistently shown that a relationship exist between the two (Belinzn et al., 1988;Hofmer et al, 1994;Onyegbule et al, 2014;Carroli et al, 1994). An inverse relationship between calcium intake and hypertensive disorders of pregnancy was first reported in 1980 (Hofmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This was based on the observation that Mayan Indians in Guatemala who traditionally soak their corn in Lime before eating had a high calcium intake and low incidence of preeclampsia (Hofmer et al, 2010). The results of clinical trials showed the aggravation of hypertensive complication and the change in concentration of various trace elements (Belinzn et al, 1988;Hofmer et al, 1994;Onyegbule et al, 2014;Carroli et al, 1994;Hofmer et al, 2010). Calcium and magnesium have a relaxant effects on blood vessels of pregnant women and changes in the concentration of these elements can lead to alteration of blood pressure causing preeclampsia (Carroli et al,1994;Hofmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%